Improving Elementary School Student’s Critical Thinking Skills through HOTS-Based Mathematics Question - Anisa Dwi Rohmawati; Achmad Fathoni (Universitas Pendidikan Ganesha, 2022)
Students' critical thinking skills in elementary schools are still very low. There have been several attempts to improve the critical thinking skills of elementary school students through various learning methods. However, only a few studies have shown an increase in critical thinking skills of elementary school students through HOTS-based questions in Mathematics. This research aimed to analyses the effectiveness of the habituation method for HOTS-based mathematical questions in improving the critical thinking skills of elementary school students. This study used a quasi-experimental design with a non-equivalent control group made up of treatment and control classes. The participant in this study is involving two elementary schools with thirty-two students. The data collection techniques in this research were tests and documentation. Statistical techniques for descriptive and inferential analysis were used to examine the test-related data. The research demonstrated that the average critical thinking skills of experiment class students were higher than the control class with a positive average difference of 2.69. Based on this result, HOTS-based Mathematics questions are effective in improving the critical thinking skills of elementary school students.